Potential Zoonosis Transmission and Compromised Animal Welfare during Eid al-Adha Festival in Ghana - Shaban, Salisu; Derrick Adu Asare; Mustapha Abubakar Ahmed; Prince Nana Takyi; Abdul Rahman Yakubu; Irene Darko; Sampson Yeboah; Benjamin Obukowho Emikpe (Media Kedokteran Hewan, 2026)
The large-scale inhumane handling and unsupervised slaughter of animals during the Eid al-Adha festival in Ghana occur under largely unregulated conditions, raising significant public health concerns. Despite the religious significance of the ritual, limited empirical data exist to assess how current practices align with public health and animal welfare standards. This study addresses this critical research gap by evaluating potential transmission of zoonosis and animal welfare practices during Eid al-Adha in Ghana. A cross-sectional, mixed-method approach was used, involving 100 participants selected through purposive and random sampling from Muslim-majority communities in Ghana. Data collection involved structured interviews and direct observation, with practices scored as positive or negative based on veterinary public health benchmarks. The results revealed a predominance of negative practices over positive ones in both zoonotic risk and animal welfare. Average scores indicated that the majority of biosecurity and handling practices were rated as ‘poor’, including low use of gloves (2%), face masks (5%), and gum boots (2%), along with poor handling of animals during slaughter (5%). Notably, feeding, recognized as a basic animal welfare practice, was the only indicator rated as ‘excellent.’ Statistical analysis using t-tests confirmed significant differences between positive and negative practices related to zoonotic risk (t = -30.76, p < 0.001) and animal welfare (t = -2.88, p = 0.046) at a 95% confidence level (α = 0.05). The study emphasizes the urgent need for veterinary oversight and structured public health action for ensuring safe practices and safeguarding animal welfare throughout the festival.